Upamiętnienie i odnowa – graffiti Banksy’ego na tle ruin - Lubaszewska, Michalina (Przestrzenie Teorii, 2025)
The text presents an analysis of the works of one of the most famous street art artists, Banksy, left in a landscape consisting of ruins (in the literal sense or referring to a place where there were ruins in the past). I first interpret the graffiti from New York and Paris, which are tributes in memory of the victims of the attack on the World Trade Center and the attack on concert attendees at the Bataclan club. These images – already created in a ‘renewed’ landscape – take on the function of ephemeral memorials. I then analyse graffiti from the embattled areas of the Gaza Strip and Ukraine. There, amidst the rubble and ruins, Banksy leaves images on the remains of buildings, blending almost organically into this altered landscape. These paintings, ludic in their form and message, are a call for renewal – both physically and spiritually – while their commemorative function remains in the background. What the graffiti from the ‘renewed’ landscape and that consisting of ruins have in common is their functioning, which can be seen in Gadamerian terms of play, symbol and festival.